Upaya Meningkatkan Kemampuan Literasi Teknologi Guru Melalui Supervisi Akademik Kreatif di SMP Negeri 4 Pasarkemis Tahun 2023 - Sugiyanta Sugiyanta (STIKes Ibnu Sina Ajibarang, 2023)
Entering the 21st century, one aspect that cannot be avoided is the influence of Information and Communication Technology (ICT). All aspects of human life cannot be separated from the influence of ICT, starting from economics, social communication, politics to education. Technology has become a mandatory choice that must be applied in the world of education, not only in the context of education in general but also penetrates education specifically, namely learning. As we know, there are many learning processes that combine technology in them.